The impact of acute bike desk usage before encoding and during early consolidation on memory task performance in university students and use case evaluation in an educational setting - Ahmed Mohsen Abbas El-Hagrasy; Rachel Anna Marshall; Thuraiya Hilal Said Al-Rawahi; Sally Doherty; Nitya Kumar; Declan Gaynor (PLoS ONE, 2025)
This study examined the impact of using bike desks on cognitive function and memory among university students. Physical activity during adolescence offers enduring health benefits, yet sedentary behaviors prevail among young adults, posing significant health risks. Bike desks, integrating stationary cycling with ergonomic desk designs, aim to mitigate sedentary behavior while enhancing cognitive performance. Research indicates that acute aerobic exercise improves executive functions, memory, and attention, which is particularly beneficial in educational settings. The study employed the verbal paired associates learning task (VPAT) to assess memory performance when either bike desk usage at moderate intensity (intervention) or rest (control condition) occurred before encoding and during early consolidation in 26 young adult medicine and nursing students in a library setting. We hypothesised that bike desk usage will enhance memory encoding and consolidation compared to the control condition of rest. The results of our study showed no significant differences in VPAT scores or response latency between seated and bike desk conditions. Supplementary analysis, including a multiple linear regression model (R2: 0.773, Adjusted R2: 0.651, p <  0.001) revealed that higher BMI, more frequent bicycle or stationary bike usage, and higher physical activity category were associated with improved VPAT performance with the bike desk, while higher vigorous MET minutes per week negatively impacted performance. This analysis suggests there are potentially numerous uncharacterized modulators of the impact of exercise on memory, warranting further research to identify and understand these factors.